2022
DOI: 10.1186/s40359-022-00829-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cognitive schemas activated in sexual context and early maladaptive schemas among married women of childbearing age

Abstract: Background Healthy sex can be affected by cognitive schemas activated in the sexual context (CSASCs) and early maladaptive schemas (EMSs). Cognitive schemas are the nuclear structure of the cognitive system which facilitate the interaction between individuals and their environments. CSASCs are emotional and behavioral responses in the sexual context. EMSs are extremely stable, enduring and are developed throughout the life of the individual, beginning in childhood. The present study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, on EMSs, boys scored higher than girls on five of the eighteen schemas including, Emotional deprivation, Emotional Inhibition, Defectiveness/Shame, Social Inhibition, and Vulnerability to Harm. In contrast, girls were observed to score higher on subscale of self-sacrifice in line with the previous findings (Shorey et al, 2012;El-Gilany et al, 2013, Janson et al, 2019Alimoradi et al 2022;). The results are counter-intuitive to research that report all maladaptive schemas, mostly in girls, except for schema of vulnerability to harm (Wijk-Herbrink et al, 2020;Shorey et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…However, on EMSs, boys scored higher than girls on five of the eighteen schemas including, Emotional deprivation, Emotional Inhibition, Defectiveness/Shame, Social Inhibition, and Vulnerability to Harm. In contrast, girls were observed to score higher on subscale of self-sacrifice in line with the previous findings (Shorey et al, 2012;El-Gilany et al, 2013, Janson et al, 2019Alimoradi et al 2022;). The results are counter-intuitive to research that report all maladaptive schemas, mostly in girls, except for schema of vulnerability to harm (Wijk-Herbrink et al, 2020;Shorey et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…While research has identified associations between early maladaptive schemas and sexual dysfunction (Alimoradi et al, 2022 ; Oliveira & Nobre, 2013 ), victimization in intimate partner violence (Hassija et al, 2018 ), interpersonal problems (Janovsky et al, 2020 ), and risky sexual behaviour (Roemmele & Messman-Moore, 2011 ), less is known about early adaptive schema (Lockwood & Perris, 2012 ). Early schema’s lifetime progress is unknown, however, it is thought that they remain stable and are triggered by psychosocial stressors (Videler et al, 2020 ).…”
Section: Schema Theorymentioning
confidence: 99%
“…Schema therapy is another intervention used for reducing tensions and conflicts in a marital relationship (23). Unlike different forms of cognitive therapy that emphasize the present, schema therapy focuses on self-destructive thinking patterns as well as feelings and behaviors rooted in childhood and resurfacing throughout a person's life (24,25).…”
Section: Introductionmentioning
confidence: 99%